2020
DOI: 10.3389/fnagi.2019.00361
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Syndrome in an Elderly Population Admitted to a Geriatric Unit: Prevalence and Effect on Cognitive Function

Abstract: Background: Sleep apnea leads to cognitive impairment in older patients, but its association with neurodegeneration remains controversial, and most studies do not distinguish between the more common obstructive form (OSAS) and the rarer central form (CSAS). Objective: The purpose of this study was to assess the prevalence of the different forms of sleep apnea in a cohort of cognitively impaired elderly patients (>70 years) and to investigate their associations with cognitive deficit, weighted against known ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…OSA has been identified as an early risk factor for developing neurodegenerative disease, such as Alzheimer's disease (AD) [1,3]. Clinical studies have shown that OSA could accelerate the progression of AD by increasing the formation and accumulation of Aβ 42 in the cerebrospinal fluid (CSF) [4,5]. OSA is often overlooked by patients in the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…OSA has been identified as an early risk factor for developing neurodegenerative disease, such as Alzheimer's disease (AD) [1,3]. Clinical studies have shown that OSA could accelerate the progression of AD by increasing the formation and accumulation of Aβ 42 in the cerebrospinal fluid (CSF) [4,5]. OSA is often overlooked by patients in the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…The SAS and pathophysiological evidence in isolation cannot fully explain the patient's cognitive impairment. SAS, especially its obstructive form, can induce cognitive impairment, in association with general cognitive impairment 9 . Our current case presented general cognitive impairment 1 year post‐baseline visit, which gradually worsened, despite successful CPAP introduction.…”
Section: Discussionmentioning
confidence: 59%
“…SAS, especially its obstructive form, can induce cognitive impairment, in association with general cognitive impairment. 9 Our current case presented general cognitive impairment 1 year post-baseline visit, which gradually worsened, despite successful CPAP introduction. The patient did not show the typical cognitive impairment of AD, although the pathophysiological findings using PiB-PET, THK5351-PET, and IMP-SPECT suggested an AD-type impairment.…”
mentioning
confidence: 62%
“…SAS can induce cognitive impairment, especially the obstructive form of SAS, which has been associated with general cognitive impairment. 8 Our current case presented general cognitive impairment one year after the baseline visit, which gradually worsened despite the successful introduction of CPAP. The patient did not show the typical cognitive impairment of AD, although the pathophysiological findings using PiB-PET, THK5351-PET, and IMP-SPECT indicated AD type impairment.…”
Section: Case Presentationmentioning
confidence: 63%